Comparison of the safety of alfaxalone and propofol as anaesthetic induction agents in bitches undergoing c-section - Haythornthwaite, Benjamin (Veterinary Evidence, 2020)
PICO question In bitches and their puppies undergoing caesarean section, is an alfaxalone or a propofol induction safer? Clinical bottom line Category of research question Risk The number and type of study designs reviewed Six papers were critically reviewed. There were two randomised controlled trials directly comparing alfaxalone and propofol inductions, two randomised controlled trials including a propofol induction in one of the experimental groups and two non-comparative studies. Strength of evidence Moderate Outcomes reported Propofol and alfaxalone can both be used safely for the anaesthesia of bitches and their puppies undergoing caesarean section. There is evidence that alfaxalone may provide better anaesthesia quality for the bitches, and the puppies may be delivered with higher indicators of puppy vitality following its use. Further research into the beneficial clinical outcomes of alfaxalone should be investigated. Conclusion The use of both propofol and alfaxalone for the induction of bitches undergoing caesarean section can be recommended. How to apply this evidence in practice The application of evidence into practice should take into account multiple factors, not limited to: individual clinical expertise, patient’s circumstances and owners’ values, country, location or clinic where you work, the individual case in front of you, the availability of therapies and resources. Knowledge Summaries are a resource to help reinforce or inform decision-making. They do not override the responsibility or judgement of the practitioner to do what is best for the animal in their care.